2011
DOI: 10.4236/ijg.2011.24069
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the Deep Structure of the Central DeathValley Basin Using Receiver Function, Gravity,and Magnetic Data

Abstract: We use receiver function, gravity, and magnetic data to image the deep structures of central Death Valley. Receiver function analysis suggests the Moho is 24 km deep in the central part of the basin and deepens to 33 km to the east and 31 km to the west. The estimated lower crustal density is 2900 kg/m 3 , which suggests a gabbroic composition, whereas the upper crustal density, excluding basin sediments, is estimated to average 2690 kg/m 3 or approximately a quartzofeldspathic composition. We modeled the magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Association of magmatism with transtensional settings, similar to the Lupar Line fault system, is known from modern and ancient locations such as Death Valley, the Red River Fault, and the Midland Valley of Scotland (e.g. Calzia and Ramo, 2000;Monaghan and Parrish, 2006;Hussein et al ., 2011). Crustal thinning associated with tension allows the mantle to upwell and, hence, melt (McKenzie and Bickle, 1988).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Association of magmatism with transtensional settings, similar to the Lupar Line fault system, is known from modern and ancient locations such as Death Valley, the Red River Fault, and the Midland Valley of Scotland (e.g. Calzia and Ramo, 2000;Monaghan and Parrish, 2006;Hussein et al ., 2011). Crustal thinning associated with tension allows the mantle to upwell and, hence, melt (McKenzie and Bickle, 1988).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…PARK (2004) concluded that partial melt is relatively uncommon beneath the Sierra Nevada and the California Basin and Range except for isolated regions beneath Miocene or younger basalt eruptions. Detailed gravity studies have provided constraints on the Death Valley basin thickness and geometry (KEENER et al 1993;BLAKELY et al 1999) and regional gravity studies combined with receiver function studies have been used to determine the crustal structure of the Death Valley region (HUSSEIN et al 2011). KEENER et al (1993) and BLAKELY et al (1999 analyzed Bouguer gravity anomalies and determined that the Death Valley basin has thicknesses varying between 3 and 5 km with steep sides along the edges of the basin.…”
Section: Tectonic and Geophysical Settingmentioning
confidence: 99%
“…The Bouguer anomaly map (figure 5) displays a smooth trend with values ranging from -114.77 mGal to -88.0 mGal. Low Bouguer anomalies are likely associated with the presence of unconsolidated sediments and sedimentary rocks (M. Hussein et al, 2011), or the presence of less dense tertiary volcanic rocks underlying the Holocene deposits which makes up the basin fill (Hillhouse et al, 1987). Alternatively, the low density within the basin can be associated with thicker pyroclastic sediments that are mainly less dense but have high magnetic susceptibility (Louie et al, 1996).…”
Section: Chapter 4 Results and Interpretationmentioning
confidence: 99%
“…Various geophysical studies have been conducted in the Tecopa Basin (Louie, 1996;Serpa, 1988;Hillhouse, 1987;Wamalwa, 2011;Hussein, 2011) (Serpa et al, 1988). Two of the seismic lines cross the Tecopa Basin.…”
Section: Previous Researchmentioning
confidence: 99%